Routledge handbook of physical cultural studies
1 online resource (640 pages)
Keywords: Physical cultural studies (PCS) is a dynamic and rapidly developing field of study. This handbook offers the first definitive account of the state of the art in PCS, showcasing the latest research and methodological approaches. It examines the boundaries, preoccupations, theories and politics of PCS, drawing on transdisciplinary expertise from areas as diverse as sport studies, sociology, history, cultural studies, performance studies and anthropology.